2009
DOI: 10.1111/j.1742-481x.2009.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of wound contracture α‐smooth muscle actin and multispecific vitronectin receptor integrin αvβ3 in the rabbit's experimental model

Abstract: The myofibroblast, a major component of granulation tissue, is a key cell during wound healing, tissue repair and connective tissue remodelling. Persistence of myofibroblasts within a fibrotic lesion leads to excessive scarring impairing function and aesthetics. Various wound-healing cytokines can be modulated by topical application of active agents to promote optimal wound healing and improve scar quality. Thus, the myofibroblast may represent an important target for wound-healing modulation to improve the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
(99 reference statements)
1
18
0
Order By: Relevance
“…The persistent presence of myofibroblasts is a distinctive feature of HTS and contributes to excessive matrix production [21], [34]. Differentiation of fibroblasts into myofibroblasts is closely associated with α-SMA [17], [35]. Our results indicate down-regulation of α-SMA expression by bFGF in the HSF and rabbit model (Figure 5 and 6J).…”
Section: Discussionmentioning
confidence: 58%
“…The persistent presence of myofibroblasts is a distinctive feature of HTS and contributes to excessive matrix production [21], [34]. Differentiation of fibroblasts into myofibroblasts is closely associated with α-SMA [17], [35]. Our results indicate down-regulation of α-SMA expression by bFGF in the HSF and rabbit model (Figure 5 and 6J).…”
Section: Discussionmentioning
confidence: 58%
“…Notably, MEBO enhanced the protein expression of VEGF and bFGF and also elevated their mRNA expression. A previous study reported that MEBO enhanced α-smooth muscle actin in fibroblasts, indicating that MEBO activates fibroblasts (43). It is hypothesized that leukocytes, including fibroblasts and endothelial cells are the primary origin of VEGF and bFGF (41).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increasing evidence indicates that MEBO promotes wound contraction and improves scar quality of wounds (43,46). Therefore, MEBO is hypothesized to be an ideal therapy for cutaneous wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Initially type III collagen is produced and then replaced by type I collagen [18]–[20]. Myofibroblasts can contract by using a smooth muscle type actin-myosin complex, rich in α-smooth muscle actin (αSMA) and are involved in the contraction and closure of wounds [21], [22]. αSMA is commonly used as a marker for the detection of myofibroblasts, but it is also present in pericytes located at the wall of blood vessels.…”
Section: Introductionmentioning
confidence: 99%